Analisis Sistem Formularium 2013 Rumah Sakit St. Elisabeth - Bekasi - Fedrini, Sally (UI Scholars Hub, 2015)
Pharmaceutical service is one of the revenue center at the hospital. Hospital formulary system is the basic principles that must be considered in pharmacy management. Hospital formulary system should be managed optimally in order to mantain consistency of clinician's prescribing utilization. The purpose of this study is to analyze the system of St Elisabeth Hospital Formulary 2013-Bekasi. Researcher conducted analysis starting from the selection, procurement and supervision of the formulary; ABC analysis; also comparation with DOEN. This study using qualitative approach through in-depth interviews and document review. The results were: the process of formulary selection is still not optimal, there is no inventory control system, and hospitals have yet to find an appropriate control system to supervise the formulary system. There were 70.860 (5%) of non-formulary drugs used in the amount of Rp1.257.098.400, there are 114 drug classes in DOEN that does not exist in the formulary. 65.89% items of drug are slow moving. There are only 100 items of drugs (14%) had an investment of 69.86% of the entire investment value. There are only 21 types of drugs (3.05%) that are very critical to patient care.